Standardization of Gunja Taila - Meena, Jitendra; Meena, Mohar Pal; Yadav, Subhash Chand; Bairwa, Dhan Raj; Mal, Nakhat (International Research Journal of Ayurveda & Yoga, 2022)
Sneha kalpana is one of the unique and commonly prescribed Ayurvedic dosage form in day-to-day practice having increase potency, palatability, shelf life etc. Although varities of Snehas are described in Ayurvedic texts, the most common amongst them are Taila & Ghrita kalpana. The research work entitled “Standardization of Gunja Taila” was planned to standardize two formulations as per the reference of Chakradatta and Bhaishajya Ratnavali. Therefore, two samples of Gunja Taila with their three batches each, were prepared with their conceptual references. Both the samples were analyzed based on Organoleptic Parameters, i.e., Appearance, Colour, Odour, Touch, etc. and Physico-chemical Parameters i.e., Foreign Matter, Specific gravity, Saponification Value, Peroxide Value, Baudouin’s Test, Mineral oil Test, Viscosity, Total fatty Matter, Refractive Index, Brix Value, Rancidity, Optical Rotation, Acid Value, Iodine Value. The findings for these parameters were found to be satisfactory for quality assurance. Assay of heavy metals (Pb, Cd, As, Hg), Total bacterial count and Total fungal count are under the permissible limit depicted in the study. Specific pathogens and aflatoxins (B1, B2, G1, G2) are absent in all samples. HPTLC is an important tool to generate the standardization parameter for quality control purpose. Sample GT-1 and GT-2 were analysed on different wavelengths 510 nm, 366 nm (Long) & 254 nm (Short). It confirmed 11 distinct spots at 510 nm, 06 distinct spots at 366 nm and 12 spots at 254 nm of GT-1 samples whereas 12 distinct spots at 510 nm, 06 distinct spots at 366 nm and 12 spots at 254 nm were observed in GT-2 samples. The Rf values of spots differentiate the chemical composition of the sample.